2019
DOI: 10.1109/access.2019.2960877
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Pencil Drawing Algorithm Based on Non-Symmetry and Anti-Packing Pattern Representation Model

Abstract: The artistic stylization transformation of images is an important part in the research of Non-Photorealistic Rendering (NPR). This kind of non-realistic stylized research has a very strong realistic romantic temperament and it can express the artistic pursuit of researchers very well. It is a good example of practical application combining computer science and art. In the technology of image style conversion, the simulation of the realistic art style includes mainly cartoon style, oil painting style, ink paint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…The artist proposes a style conversion scheme based on a priori knowledge of intersections in a regular distribution of tones. Emphasis is placed on the use of asymmetry patterns to enhance the image painting by using the edge extraction method as a model, which highlights the details of the image and can transform the style of the image through the combination of image and tone [14]. He J illustrates the language of painting as a painting technique that incorporates the arts of color, line, light, subject, and image.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The artist proposes a style conversion scheme based on a priori knowledge of intersections in a regular distribution of tones. Emphasis is placed on the use of asymmetry patterns to enhance the image painting by using the edge extraction method as a model, which highlights the details of the image and can transform the style of the image through the combination of image and tone [14]. He J illustrates the language of painting as a painting technique that incorporates the arts of color, line, light, subject, and image.…”
Section: Literature Reviewmentioning
confidence: 99%
“…As a more abstract image generation technique, nonrealistic drawing techniques are becoming a focus of research in the field of computer graphics. Nonrealistic drawing is a technique that adapts to the content of an image, preserving certain key details in the image [20].…”
Section: Introductionmentioning
confidence: 99%
“…Huang et al (2019) [5] found that virtual brush modeling plays a vital role in virtual painting, and a powerful virtual brush model can truly reflect the features of real brushes and enhance the realism of virtual painting. Zheng et al (2019) [6] proved that the artistic stylization of image is an important content of non-photorealistic rendering research, such non-realistic stylized research has a strong realistic romantic temperament and can well express the researcher's artistic pursuit. It is a good application example of the combination of computer science and art.…”
Section: Introductionmentioning
confidence: 99%